Filosofie "Just in time" a její současné problémy - Latýn, Patrik (Univerzita Pardubice, 1998)
Articles describes wrong understanding of JIT philosophy, as a connecting system between supplier and customer through faster and more frequent deliveries. It shows. It's first appearance, philosophy and also deals with supplies relationships with in JIT system. In the second part of the article current problems of transport in JIT regime are highlighted. At the same time there are offered solutions which are applied by companies, which already had serious problem with JIT.
Keywords: Transport; philosophy "Just in time"; customers; Suppliers; Supplies